Summertime : from Porgy and Bess - Gershwin, Ira, 1896-1983; Wimmer, Mike; Gershwin, George, 1898-1937; Heyward, DuBose, 1885-1940; Heyward, Dorothy, 1890-1961 (Simon & Schuster, 1999)
Paintings depict a family's routine one summer day earlier in this century.